Thermal, spectroscopic and in vitro biological studies of the lanthanum complex of naproxen - Gálico, D. A. [UNESP]; Fraga-Silva, T. F.C. [UNESP]; Venturini, J. [UNESP]; Bannach, G. [UNESP] (Elsevier, 2016)
Solid-state [La(Nap)3(H2O)], in which Nap is naproxen have been synthesized. Thermogravimetry (TG), differential thermal analysis (DTA), differential scanning calorimetry (DSC), powder X-ray diffractometry (XRD), elemental analysis, complexometric titration, middle (MIR) and near (NIR) infrared region spectroscopy were used to characterize this compound and confirm the proposed stoichiometry. The experimental results provided information concerning the chemical composition, dehydration, coordination modes of the ligand, crystallinity of the sample, thermal behavior, thermal decomposition and polymorphism. Theoretical calculations helped in the assignment of the MIR vibrational bands and in the understanding of the coordination mode of the ligands. Cyclic DSC and XRD in different temperatures demonstrated that the complex presents five temperature dependent polymorphic forms. MIR spectroscopy suggest that the naproxen coordinates through the carboxylate group as a chelating ligand. [La(Nap)3(H2O)] showed lower cell cytotoxicity in comparison to naproxen. The compound increased the production of pro-inflammatory metabolites, such as TNF-α, IL-1β and H2O2, and decreased an IL-8 level, that interferes in the trafficking of inflammatory cells.
Keywords: In vitro biological studies; Lanthanum; Naproxen; Polymorphism; Spectroscopic studies; Thermal behavior